EVALUATION OF THE IMPLEMENTATION OF LEARNING AQIDAH MORALS FOR STUDENTS OF CLASS 2 MI NEGERI 3 BOYOLALI - Vardani, Ruslan; Subando, Joko (Institut Islam Mamba'ul 'Ulum Surakarta, 2023)
Evaluation in education is a component that is no less important than the learningprocess. When the learning process is seen as a process of changing student behavior,the role of evaluating the learning process becomes very important. Evaluation is aprocess for collecting, analyzing and interpreting information to determine the level ofachievement of learning objectives by students. A good evaluation system will be able toprovide an overview of the quality of learning so that in turn it will be able to helpteachers plan learning strategies. For students themselves, a good evaluation systemwill be able to provide motivation and then improve their abilities.